Hayek vs. Kelsen: the liberal foundation of the lex mercatoria - Núñez del Prado, Fabio (2017)
How are commercial rules created? Should they be created in a constructivist way or are they created rather through a spontaneous order? Should Kelsen’s positivism prevail in commercial law? Should sectorial rules of risk allocation be included in a Civil Code?.The present article answers with effectiveness each one of these questions with the purpose of demonstrating that in commercial law the source par excellence should be the Lex Mercatoria.